Future rainfall variations reduce abundances of aboveground arthropods in model agroecosystems with different soil types - Zaller, Johann G.; Simmer, Laura; Santer, Nadja; Tabi Tataw, James; Formayer, Herbert; Murer, Erwin; Hösch, Johannes; Baumgarten, Andreas (Frontiers in Environmental Science, 2014)
Climate change scenarios for Central Europe predict less frequent but heavier rainfalls and longer drought periods during the growing season. This is expected to alter arthropods in agroecosystems that are important as biocontrol agents, herbivores or food for predators (e.g. farmland birds). In a lysimeter facility (totally 18 3-m2-plots), we experimentally tested the effects of long-term past vs. prognosticated future rainfall variations (15% increased rainfall per event, 25% more dry days) according to regionalized climate change models from the Intergovernmental Panel on Climate Change (IPCC) on aboveground arthropods in winter wheat (Triticum aestivum L.) cultivated at three different soil types (calcaric phaeozem, calcic chernozem and gleyic phaeozem). Soil types were established 17 years and rainfall treatments one month before arthropod sampling; treatments were fully crossed and replicated three times. Aboveground arthropods were assessed by suction sampling, their mean abundances (± SD) differed between April, May and June with 20 ± 3 m-2, 90 ± 35 m-2 and 289 ± 93 individuals m-2, respectively. Averaged across sampling dates, future rainfall reduced the abundance of spiders (Araneae, -47%), cicadas and leafhoppers (Auchenorrhyncha, -39%), beetles (Coleoptera, -52%), ground beetles (Carabidae, -41%), leaf beetles (Chrysomelidae, -64%), spring tails (Collembola, -58%), flies (Diptera, -73%) and lacewings (Neuroptera, -73%) but increased the abundance of snails (Gastropoda, +69%). Across sampling dates, soil types had no effects on arthropod abundances. Arthropod diversity was neither affected by rainfall nor soil types. Arthropod abundance was positively correlated with weed biomass for almost all taxa; abundance of Hemiptera and of total arthropods was positively correlated with weed density. These detrimental effects of future rainfall varieties on arthropod taxa in wheat fields can potentially alter arthropod-associated agroecosystem services.